Ibn Taymiyyah’s Version of Corporealism of God - Dipto, Roshlan Rahman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In Abrahamic tradition, the question of God’s relationship with body, space and direction is an inescapable philosophical and theological issue and Islam is not an exception. The Central text of Islam, Quran, contains verses that anthropomorphically attributes “hands”, “eyes”, “face” “establishment upon throne” referencing God. These verses have for centuries sparked among the Muslim philosophers and theologians, centuries of debate; leading to diverse interpretations and theological schools of thought. Ibn Taymiyyah and Fahr al-Din al-Rāzī are two of those prominent figures who also debated this issue. Ibn Taymiyyah takes the relational ontology of space and doesn't negate the prediction of the body to God. On the other hand, Fahr al-Dīn al-Rāzī an Ash’ari theologian negates all kinds of anthropomorphic attribution for God. This paper presents Ibn Taymiyyah’s position on God's body and his conflict with Ash’ari scholar Fahr al-Dīn al-Rāzī.